Phenolic resin modified asphalt coated graphite negative electrode material and preparation method thereof

CN122907625APending Publication Date: 2026-10-13ZHENGZHOU UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611261120.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0011]针对现有单一沥青包覆石墨负极技术中包覆层致密度不足、锂离子传导性能有限及包覆均匀性差的缺陷,本发明解决的技术问题是提供一种酚醛树脂改性沥青包覆石墨负极及其制备方法,该材料可广泛应用于消费电子、动力锂离子电池及储能电池等领域

Benefits of technology

[0027]一是界面性能提升。酚醛树脂热解形成的硬炭相可填充沥青软炭层的微孔缺陷,形成结构致密的复合包覆层,物理阻隔电解液与石墨基体接触,抑制电解液持续分解与SEI膜破裂,显著降低电池界面阻抗,提高了界面稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907625A_ABST
    Figure CN122907625A_ABST
Patent Text Reader

Abstract

The present application relates to phenolic resin modified asphalt coated graphite negative material and its preparation method, belong to lithium ion battery negative material technical field.The technical problem solved by the present application is to provide a kind of phenolic resin modified asphalt coated graphite negative and its preparation method, the preparation method of the material includes asphalt purification, liquid phase blending modification, liquid phase coating and segmented carbonization process, finally obtains phenolic resin modified asphalt coated graphite negative material.The present application is modified by introducing phenolic resin into asphalt, utilizes the high residual carbon rate and the characteristics of pyrolysis of phenolic resin to form hard carbon, mutually collaborates and mutually repairs in the carbonization process with the soft carbon formed by asphalt pyrolysis, finally forms the composite coating layer structure of " hard carbon skeleton support + soft carbon conductive filling", can improve the interface performance of material, optimize structure toughness, improve coating uniformity, thereby improve the electrochemical performance of graphite negative material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to phenolic resin modified pitch-coated graphite anode material and its preparation method, belonging to the technical field of lithium-ion battery anode materials. Background Technology

[0002] Graphite is currently the most mainstream anode material for commercial lithium-ion batteries. However, graphite itself has a layered crystal structure with numerous active sites and edge defects on its surface. During charging and discharging, it is prone to side reactions with the electrolyte, forming a structurally unstable solid electrolyte interphase (SEI) film. Furthermore, during repeated lithium insertion and extraction, graphite undergoes periodic volume expansion and layered exfoliation, ultimately leading to shortened battery cycle life, poor rate performance, and poor initial coulombic efficiency. To improve these defects, carbon coating processes are commonly used in the field to modify the surface of graphite, with pitch coating being the most widely used industrial application. Currently, the method of preparing carbon-coated graphite anodes using pitch as a coating agent is a well-known technology in the field. A typical pitch-coated graphite anode preparation process involves mixing natural graphite and coal tar pitch in a certain mass ratio, heating under an inert atmosphere to above the pitch softening point, melting the pitch and uniformly coating it onto the surface of graphite particles, followed by carbonization treatment to obtain pitch-pyrolyzed carbon-coated graphite anode material. This technology utilizes an amorphous carbon coating layer to cover the active sites and defects on the graphite surface, reducing the direct contact between the electrolyte and graphite and the irreversible decomposition reaction, thereby improving the electrochemical performance of the material to a certain extent.

[0003] However, the aforementioned existing technical solutions still have the following obvious shortcomings in practical applications:

[0004] (1) Insufficient density of the coating layer: The asphalt composition is relatively complex. During the high-temperature carbonization process, a large number of light components volatilize and escape, resulting in a large number of pores and microcracks remaining inside the formed carbon coating layer, which has poor density. The electrolyte can still penetrate along the defects and react with the graphite.

[0005] (2) Weak interfacial bonding: The asphalt carbon and the graphite matrix mainly rely on physical adsorption and mechanical interlocking, resulting in weak interfacial bonding. During repeated charging and discharging of the battery, the volume change of graphite particles can easily cause the coating layer to crack, peel off or fall off, causing the graphite to be exposed to the electrolyte again.

[0006] (3) Poor coating uniformity: In the traditional melt coating process, asphalt is prone to flow and agglomeration, resulting in uneven coating thickness on the surface of graphite particles.

[0007] Therefore, how to improve the existing asphalt-coated graphite anode technology to obtain anode materials with dense coating, strong interfacial bonding and excellent comprehensive electrochemical performance has become an urgent technical problem to be solved.

[0008] To address the aforementioned technical problems, several improvements have been reported in this field. For example, patent CN115579470A discloses a modified bitumen-coated microcrystalline graphite anode material and its preparation method. The method involves first heating and treating the microcrystalline graphite, mixing it with a binder, pulverizing it, then immersing it in acid, coating the dried microcrystalline graphite with phenolic resin, then coating it with modified bitumen, and finally carbonizing and graphitizing it to obtain the modified bitumen-coated microcrystalline graphite anode material. This method involves a double-layer independent coating, first using phenolic resin to form a dense inner carbon layer, and then using modified bitumen to form a loose outer carbon layer. It requires two coating processes and two high-temperature treatments, making the process complex and costly. Furthermore, its main technical objective is to solve problems such as low purity, numerous pores, low tap density, and large specific surface area of ​​microcrystalline graphite, but it cannot address the core defects of single bitumen coating, such as insufficient density, weak interfacial bonding, and poor coating uniformity.

[0009] For example, patent CN103035919A discloses a method for preparing modified graphite anode materials for lithium-ion power batteries. The method involves heating asphalt and resin to melt them into a liquid, then continuously stirring and mixing them before stopping the heating and cooling to obtain a composite coating material block. The composite coating material block is then pulverized to obtain ultrafine powder. This ultrafine powder is then thoroughly mixed with graphite, heated and held at that temperature under inert gas protection, and then allowed to cool naturally. After cooling, the mixture is sieved to obtain the modified graphite anode material for lithium-ion power batteries. In this method, the bonding between the coating layer and the graphite matrix is ​​mainly physical adsorption and mechanical intercalation, resulting in weak interfacial adhesion. Furthermore, the escape of small molecules during resin pyrolysis creates excessive voids on the surface of the coating layer, leading to a large specific surface area and preventing the formation of a dense composite coating layer. Furthermore, the use of ultrafine solid powder can only adhere to the macroscopic outer surface of graphite, and cannot fill microscopic defects, resulting in discontinuous coating layers and numerous defect sites. The pulverization process easily introduces mechanical impurities, and the wide particle size distribution of the powder directly leads to large differences in coating thickness, making it difficult to form a complete and continuous nanoscale coating film, ultimately affecting product performance.

[0010] It is evident that existing bitumen-coated graphite anode technology and reported improvements still cannot simultaneously solve technical problems such as insufficient coating density, weak interfacial bonding, and poor coating uniformity. Summary of the Invention

[0011] To address the shortcomings of existing single-asphalt-coated graphite anode technology, such as insufficient coating density, limited lithium-ion conductivity, and poor coating uniformity, this invention provides a phenolic resin-modified asphalt-coated graphite anode and its preparation method. This material can be widely used in consumer electronics, power lithium-ion batteries, and energy storage batteries.

[0012] The present invention discloses a method for preparing phenolic resin-modified pitch-coated graphite anode material, comprising the following steps:

[0013] (1) Asphalt purification: Dissolve asphalt in toluene, separate the solid and liquid, remove toluene from the liquid to obtain purified asphalt;

[0014] (2) Liquid phase blending modification: The purified asphalt obtained in step (1) is dissolved in solvent 1 to prepare an asphalt solution; phenolic resin is dissolved in solvent 2 to prepare a resin solution; after the asphalt solution and resin solution are mixed, solvent 1 and solvent 2 are removed, and the resulting mixture is kept in a vacuum environment at 200-300℃ for 1-3 h to complete the curing modification and obtain phenolic resin modified asphalt;

[0015] (3) Liquid phase coating: Dissolve the phenolic resin modified asphalt obtained in step (2) in solvent 3, add graphite powder and mix well to obtain a mixed slurry; remove solvent 3 from the mixed slurry and dry it to obtain the coating precursor;

[0016] (4) Segmented carbonization: Under a protective atmosphere, the coating precursor obtained in step (3) is heated to 400-600℃ at a heating rate of 3-7℃ / min and held for 20-40 min for pre-carbonization; the temperature is further increased to 900-1100℃ at a rate of 3-7℃ / min and held for 100-150 min to complete the final carbonization; after cooling, it is sieved to obtain phenolic resin modified pitch coated graphite anode material.

[0017] In some embodiments of the present invention, solvent 1 is dichloromethane or acetone; solvent 2 is ethanol; and solvent 3 is tetrahydrofuran or toluene.

[0018] In some embodiments of the present invention, in step (1), the dissolution temperature is 40–60°C and the dissolution time is 20–40 min. Preferably, the dissolution temperature is 50°C and the dissolution time is 30 min.

[0019] In some embodiments of the present invention, in step (2), the amount of phenolic resin used is 5% to 25% of the mass of purified asphalt. Preferably, the amount of phenolic resin used is 5%, 15%, or 25% of the mass of purified asphalt.

[0020] In some embodiments of the present invention, in step (2), the obtained mixture is cured and modified by keeping it in a vacuum environment at 250°C for 2 hours.

[0021] In one specific embodiment of the present invention, in step (4), the coating precursor is heated to 500°C at a heating rate of 5°C / min and held for 30 min for pre-carbonization; then the temperature is increased to 1000°C at a rate of 5°C / min and held for 120 min to complete the final carbonization.

[0022] In one embodiment of the present invention, the solvent removal methods in steps (1), (2), and (3) are all rotary evaporation. In a preferred embodiment of the present invention, the solvent removal is performed by vacuum rotary evaporation.

[0023] The present invention also provides a phenolic resin modified bitumen-coated graphite anode material.

[0024] This invention relates to a phenolic resin-modified pitch-coated graphite anode material, prepared using the method described herein. This phenolic resin-modified pitch-coated graphite anode material possesses a composite coating structure of "hard carbon skeleton support + soft carbon conductive filler," which effectively reduces the charge transfer impedance of the graphite anode.

[0025] This invention modifies asphalt by introducing phenolic resin, utilizing the high residual carbon content and the characteristic of phenolic resin to form hard carbon through pyrolysis. During carbonization, the resin synergistically repairs and complements the soft carbon formed from asphalt pyrolysis. In the segmented carbonization process, the low-temperature pre-carbonization stage (400–600℃) primarily removes light components from the coating agent and performs preliminary carbonization of the phenolic resin, fixing the morphology of the coating layer. The high-temperature final carbonization stage (900–1100℃) fully carbonizes the asphalt, forming a conductive network with a certain degree of graphitization, while the hard carbon skeleton maintains good structural stability. The synergistic effect of these two processes ultimately forms a composite coating layer structure of "hard carbon skeleton support + soft carbon conductive filler."

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] First, it improves interface performance. The hard carbon phase formed by the pyrolysis of phenolic resin can fill the micropore defects of the soft carbon layer of pitch, forming a dense composite coating layer. This physically blocks the contact between the electrolyte and the graphite matrix, inhibits the continuous decomposition of the electrolyte and the rupture of the SEI film, significantly reduces the interfacial impedance of the battery, and improves the interfacial stability.

[0028] Second, the structural toughness is optimized. The composite coating combines the high conductivity of soft carbon with the high strength and toughness of hard carbon, which can effectively buffer the volume expansion stress during the lithium insertion and extraction process of graphite and prevent the coating from cracking and falling off.

[0029] Third, it improves the uniformity of coating. The liquid-phase blending process can achieve uniform mixing of modifier and asphalt at the molecular level, avoiding the problem of asphalt flow and agglomeration during the melt coating process, ensuring the uniform thickness of the coating layer on the surface of graphite particles, and improving the stability of material performance. Attached Figure Description

[0030] Figure 1 This is a flowchart illustrating the preparation process of phenolic resin-modified bitumen-coated graphite anode material in an embodiment of the present invention.

[0031] Figure 2Electron micrograph (500x) of the graphite anode material used in this invention.

[0032] Figure 3 Electron micrograph (3000x) of the graphite anode material used in this invention.

[0033] Figure 4 Electron micrograph (3000x) of the modified graphite anode material of Example 3 of this invention.

[0034] Figure 5 Electron micrograph (3000x) of the modified graphite anode material of Comparative Example 1 of this invention.

[0035] Figure 6 These are EIS images of AC impedance testing in Example 1 of the present invention, showing the embodiment and comparative examples.

[0036] Figure 7 The images shown are EIS images of the graphite-coated samples before and after asphalt purification in Experiment Example 2 of this invention. Detailed Implementation

[0037] The present invention discloses a method for preparing phenolic resin-modified pitch-coated graphite anode material, comprising the following steps:

[0038] (1) Asphalt purification: Dissolve asphalt in toluene, separate the solid and liquid, remove toluene from the liquid to obtain purified asphalt;

[0039] (2) Liquid phase blending modification: The purified asphalt obtained in step (1) is dissolved in solvent 1 to prepare an asphalt solution; phenolic resin is dissolved in solvent 2 to prepare a resin solution; after the asphalt solution and resin solution are mixed, solvent 1 and solvent 2 are removed, and the resulting mixture is kept in a vacuum environment at 200-300℃ for 1-3 h to complete the curing modification and obtain phenolic resin modified asphalt;

[0040] (3) Liquid phase coating: Dissolve the phenolic resin modified asphalt obtained in step (2) in solvent 3, add graphite powder and mix well to obtain a mixed slurry; remove solvent 3 from the mixed slurry and dry it to obtain the coating precursor;

[0041] (4) Segmented carbonization: Under a protective atmosphere, the coating precursor obtained in step (3) is heated to 400-600℃ at a heating rate of 3-7℃ / min and held for 20-40 min for pre-carbonization; the temperature is further increased to 900-1100℃ at a rate of 3-7℃ / min and held for 100-150 min to complete the final carbonization; after cooling, it is sieved to obtain phenolic resin modified pitch coated graphite anode material.

[0042] The method of this invention achieves homogeneous modification of phenolic resin and asphalt through liquid-phase blending, constructs a soft and hard carbon synergistic coating structure, and significantly reduces the charge transfer impedance of graphite anode.

[0043] In some embodiments of the present invention, solvent 1 is dichloromethane or acetone; solvent 2 is ethanol; and solvent 3 is tetrahydrofuran or toluene.

[0044] Step (1) is the asphalt purification step, in which asphalt is dissolved in toluene, solid-liquid separation is performed, and the toluene is removed from the resulting liquid to obtain purified asphalt. The purified asphalt has a more homogeneous composition and a narrower molecular weight distribution, which is beneficial for the uniform modification with phenolic resin and the stability of the subsequent coating quality, and reduces the adverse effects of impurities on electrochemical performance.

[0045] In some embodiments of the present invention, in step (1), the dissolution temperature is 40–60°C and the dissolution time is 20–40 min. Preferably, the dissolution temperature is 50°C and the dissolution time is 30 min.

[0046] Step (1) is liquid-phase blending modification. The purified asphalt obtained in step (1) is dissolved in solvent 1 to prepare an asphalt solution; phenolic resin is dissolved in solvent 2 to prepare a resin solution; after the asphalt solution and resin solution are mixed, solvent 1 and solvent 2 are removed, and the resulting mixture is kept in a vacuum environment at 200-300℃ for 1-3 hours to complete the curing modification, thus obtaining phenolic resin modified asphalt. Through liquid-phase blending, the damage to the asphalt components caused by high-temperature thermal history is avoided, ensuring that the asphalt can form a more ordered conductive network (soft carbon has better conductivity) in the subsequent carbonization process. After removing the solvent in the liquid-phase blending, the curing modification is completed. This step allows the phenolic resin to undergo pre-crosslinking and curing in the asphalt matrix, forming a stable modified asphalt structure, so that the phenolic resin can more fully play the supporting role of the hard carbon skeleton in the subsequent carbonization process.

[0047] In some embodiments of the present invention, in step (2), the amount of phenolic resin used is 5% to 25% of the mass of purified asphalt. Preferably, the amount of phenolic resin used is 5%, 15%, or 25% of the mass of purified asphalt. More preferably, the amount of phenolic resin used is 15% of the mass of purified asphalt.

[0048] In some embodiments of the present invention, in step (2), the obtained mixture is cured and modified by keeping it in a vacuum environment at 250°C for 2 hours.

[0049] Step (3) involves liquid-phase coating. The phenolic resin-modified asphalt obtained in step (2) is dissolved in solvent 3, and graphite powder is added and mixed to obtain a mixed slurry. Solvent 3 is removed from the mixed slurry, and then it is dried to obtain the coating precursor. By using the liquid-phase coating method, the modified asphalt solution can fully wet the microstructure of the graphite particles, such as surface depressions and edge defects, to form a complete and continuous nanoscale coating film without any coating dead corners.

[0050] Step (4) is segmented carbonization. Under a protective atmosphere, the coating precursor obtained in step (3) is heated to 400-600℃ at a heating rate of 3-7℃ / min and held for 20-40 min for pre-carbonization. The temperature is then increased to 900-1100℃ at a rate of 3-7℃ / min and held for 100-150 min to complete the final carbonization. After cooling, the material is sieved to obtain phenolic resin modified pitch coated graphite anode material.

[0051] This carbonization process is divided into two stages—pre-carbonization and final carbonization—and has the following advantages:

[0052] The pre-carbonization stage fixes the morphology of the coating layer and prevents melting deformation: During the pre-carbonization stage, the phenolic resin has initially carbonized to form a hard carbon skeleton, which "fixes" the morphology of the coating layer. Subsequently, when the temperature is raised to the final carbonization temperature, even if the asphalt melts and flows, the hard carbon skeleton provides support, and the coating layer will not collapse or agglomerate.

[0053] Light components are removed in an orderly manner, reducing porosity defects: segmented carbonization allows light components in the coating agent to be removed in an orderly manner during the 500℃ pre-carbonization stage. At this time, the coating layer is not yet fully densified, and the damage caused by the escape of light components can be filled and repaired by the hard carbon phase in the subsequent high-temperature stage.

[0054] The step-by-step construction of the soft and hard carbon synergistic structure: 500℃ pre-carbonization mainly completes the initial conversion of phenolic resin into hard carbon, forming a preliminary structural framework; 1000℃ final carbonization fully carbonizes the pitch and forms a conductive network with a certain degree of graphitization. The two processes form step-by-step and work synergistically to ultimately obtain an ideal composite structure of "hard carbon framework support + soft carbon conductive filler".

[0055] In one specific embodiment of the present invention, in step (4), the coating precursor is heated to 500°C at a heating rate of 5°C / min and held for 30 min for pre-carbonization; then the temperature is increased to 1000°C at a rate of 5°C / min and held for 120 min to complete the final carbonization.

[0056] In one embodiment of the present invention, the solvent removal methods in steps (1), (2), and (3) are all rotary evaporation. The rotary evaporation temperature can be determined based on the boiling point of the solvent. In a preferred embodiment of the present invention, solvent removal is performed using vacuum rotary evaporation.

[0057] This invention relates to a phenolic resin-modified pitch-coated graphite anode material, prepared using the method described herein. This phenolic resin-modified pitch-coated graphite anode material possesses a composite coating structure of "hard carbon skeleton support + soft carbon conductive filler," which effectively reduces the charge transfer impedance of the graphite anode.

[0058] This invention modifies asphalt by introducing phenolic resin, utilizing the high residual carbon content and the characteristic of phenolic resin to form hard carbon through pyrolysis. During carbonization, the resin synergistically repairs and complements the soft carbon formed from asphalt pyrolysis. In the segmented carbonization process, the low-temperature pre-carbonization stage (400–600℃) primarily removes light components from the coating agent and performs preliminary carbonization of the phenolic resin, fixing the morphology of the coating layer. The high-temperature final carbonization stage (900–1100℃) fully carbonizes the asphalt, forming a conductive network with a certain degree of graphitization, while the hard carbon skeleton maintains good structural stability. The synergistic effect of these two processes ultimately forms a composite coating layer structure of "hard carbon skeleton support + soft carbon conductive filler."

[0059] The present invention will be further illustrated below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field.

[0060] Example 1

[0061] like Figure 1 As shown, the phenolic resin-modified bitumen-coated artificial graphite anode was prepared according to the following steps:

[0062] (1) Asphalt purification: High-temperature asphalt is placed in toluene and dissolved at 50°C for 30 minutes. The quinoline insoluble matter is removed by vacuum filtration. The filtrate is then evaporated at 60°C to remove toluene, and purified asphalt is obtained.

[0063] (2) Liquid-phase blending modification: Take 1g of the purified asphalt obtained in step (1) and dissolve it in 6mL of dichloromethane to prepare an asphalt solution. Weigh 5% of the asphalt mass of phenolic resin and dissolve it in 6mL of ethanol to prepare a resin solution. Mix the asphalt solution and resin solution evenly under stirring conditions, and remove the dichloromethane-ethanol composite solvent by rotary evaporation under reduced pressure at 50℃. The resulting mixture is then cured and modified in a vacuum environment at 250℃ for 2h to obtain phenolic resin modified asphalt.

[0064] (3) Liquid phase coating: Take 1g of the modified asphalt obtained in step (2), dissolve it in 100mL of tetrahydrofuran, and fully dissolve it at 50℃. Add 9g of artificial graphite powder, stir for 10min and ultrasonically disperse for 30min to obtain a uniformly mixed slurry. Remove the tetrahydrofuran from the mixed slurry by rotary evaporation under reduced pressure at 50℃, and then dry it fully at 70℃ for 2h to obtain the coated precursor.

[0065] (4) Segmented carbonization: The coated precursor obtained in step (3) is placed in a tube furnace under a nitrogen atmosphere and heated to 500°C at a heating rate of 5°C / min, and held for 30 min for pre-carbonization; the temperature is then increased to 1000°C at a rate of 5°C / min and held for 120 min to complete the final carbonization; the carbonization product is then naturally cooled to room temperature. The carbonization product is sieved through a 300-mesh sieve to obtain the finished product of phenolic resin modified pitch coated artificial graphite anode.

[0066] Example 2

[0067] The difference between this embodiment and embodiment 1 is that the amount of phenolic resin added in step (2) is 15% of the mass of asphalt.

[0068] Example 3

[0069] The difference between this embodiment and embodiment 1 is that the amount of phenolic resin added in step (2) is 25% of the mass of asphalt.

[0070] Comparative Example 1

[0071] The difference between this comparative example and Example 1 is that step (2) was not performed, that is, the amount of phenolic resin added was 0% of the mass of asphalt.

[0072] Electron micrographs of the graphite anode material used in this invention are shown below. Figure 2 and Figure 3 ,in, Figure 2 To enlarge a photo by 500 times, Figure 3 The image is magnified 3000 times. An electron microscope image of the phenolic resin-modified bitumen-coated artificial graphite anode product obtained in Example 3 of this invention is shown below. Figure 4 The electron microscope images of the modified graphite anode material in comparison can be found in... Figure 5 As can be seen from the electron microscope images, the original graphite exhibits a distinct layered structure and numerous surface defects, making it prone to side reactions with the electrolyte when used directly as a negative electrode material. Compared to the original graphite, the modified graphite in Example 3 and the comparative example shows a clear coating layer, with some edges covered by the asphalt coating layer, indicating that the asphalt coating improves the surface condition of the original graphite to some extent. Furthermore, after using phenolic resin to modify the asphalt coating in Example 3, the uniformity, density, and integrity of the coating on the graphite surface are superior to those in Comparative Example 1, which is more conducive to suppressing the side reactions between the electrolyte and the graphite.

[0073] Experimental Example 1

[0074] The negative electrode materials obtained in Examples 1-3 and Comparative Example 1 were mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 8:1:1, respectively, and N-methylpyrrolidone was used as a solvent to prepare a slurry. The slurry was then coated onto a copper current collector to prepare a working electrode. A platinum sheet electrode was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. The electrolyte was 1 mol / L LiPF6 / EC+DMC+EMC (volume ratio 1:1:1). The three-electrode system was assembled. The electrolyte preparation and three-electrode assembly processes were all carried out in a glove box.

[0075] Electrochemical impedance spectroscopy (EIS) was performed using an electrochemical workstation. A sinusoidal AC perturbation signal with an amplitude of 5 mV was applied at open-circuit potential, with a frequency sweep range of 100 kHz to 10 mHz, and Nyquist plots were acquired. The impedance spectrum was fitted using ZView software, selecting an equivalent circuit model suitable for the graphite anode. The impedance parameters of each interface are shown in Table 1, and the fitted images are shown below. Figure 2 As shown.

[0076] Table 1. AC impedance fitting results of the examples and comparative examples.

[0077] Example 1 34.35 28.10 Example 2 26.88 14.82 Example 3 33.62 22.12 Comparative Example 1 30.57 34.19

[0078] As shown in Table 1, the charge transfer resistance Rct of the comparative example is 34.19 Ω, while the Rct of Examples 1 to 3 are significantly lower than that of the comparative example, at 28.10 Ω, 14.82 Ω, and 22.12 Ω, respectively. Among them, Example 2 (phenolic resin addition of 15%) has the lowest Rct, at only 14.82 Ω, which is about 56.7% lower than that of Comparative Example 1. This result indicates that the present invention, by modifying asphalt with phenolic resin and constructing a soft and hard carbon composite coating layer, can significantly reduce the charge transfer resistance of graphite anodes.

[0079] Experimental Example 2

[0080] Following the method of Experimental Example 1, the effects of asphalt purification before and after treatment on phenolic resin-modified asphalt-coated graphite anodes were studied. The results are shown in [Figure 1]. Figure 3 And Table 2.

[0081] Table 2. Results of AC impedance fitting of graphite coating before and after asphalt purification

[0082] Before purification 27.56 35.77 After purification 30.57 34.19

[0083] Among them, the purified sample was directly used for graphite coating, and after liquid phase coating and segmented carbonization, a graphite anode material sample was obtained.

[0084] The preparation method for the unpurified sample is the same as that for the purified sample, the only difference being the absence of the purification step, i.e., the asphalt is not purified.

[0085] The AC impedance spectroscopy results of graphite coated with asphalt before and after purification showed that the charge transfer resistance decreased from 35.77 Ω to 34.19 Ω after purification. This significant reduction in charge transfer resistance indicates that asphalt purification has a positive impact on the charge transfer process of the graphite-coated anode, effectively reducing the charge transfer resistance at the electrode interface and facilitating the electrochemical reaction at the electrode.

[0086] It should be noted that while the preferred embodiments of the present invention are given in the specification and accompanying drawings, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. These embodiments are not intended to impose additional limitations on the content of the present invention; their purpose is to provide a more thorough and comprehensive understanding of the disclosure of the present invention. Furthermore, the above-described technical features can be combined with each other to form various embodiments not listed above, all of which are considered to be within the scope of the present invention specification. Moreover, those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A method for preparing phenolic resin-modified pitch-coated graphite anode material, characterized in that, Includes the following steps: (1) Asphalt purification: Dissolve asphalt in toluene, separate the solid and liquid, remove toluene from the liquid to obtain purified asphalt; (2) Liquid phase blending modification: The purified asphalt obtained in step (1) is dissolved in solvent 1 to prepare an asphalt solution; phenolic resin is dissolved in solvent 2 to prepare a resin solution; after the asphalt solution and resin solution are mixed, solvent 1 and solvent 2 are removed, and the resulting mixture is kept in a vacuum environment at 200-300℃ for 1-3 h to complete the curing modification and obtain phenolic resin modified asphalt; (3) Liquid phase coating: Dissolve the phenolic resin modified asphalt obtained in step (2) in solvent 3, add graphite powder and mix well to obtain a mixed slurry; remove solvent 3 from the mixed slurry and dry it to obtain the coating precursor; (4) Segmented carbonization: Under a protective atmosphere, the coating precursor obtained in step (3) is heated to 400-600℃ at a heating rate of 3-7℃ / min and held for 20-40 min for pre-carbonization; the temperature is further increased to 900-1100℃ at a rate of 3-7℃ / min and held for 100-150 min to complete the final carbonization; after cooling, it is sieved to obtain phenolic resin modified pitch coated graphite anode material.

2. The method for preparing phenolic resin-modified pitch-coated graphite anode material according to claim 1, characterized in that: Solvent 1 is dichloromethane or acetone; solvent 2 is ethanol; solvent 3 is tetrahydrofuran or toluene.

3. The method for preparing phenolic resin-modified pitch-coated graphite anode material according to claim 1, characterized in that: In step (1), the dissolution temperature is 40-60℃ and the dissolution time is 20-40 min; preferably, the dissolution temperature is 50℃ and the dissolution time is 30 min.

4. The method for preparing phenolic resin-modified pitch-coated graphite anode material according to claim 1, characterized in that: In step (2), the amount of phenolic resin used is 5% to 25% of the mass of purified asphalt; preferably, the amount of phenolic resin used is 5%, 15% or 25% of the mass of purified asphalt.

5. The method for preparing phenolic resin-modified pitch-coated graphite anode material according to claim 1, characterized in that: In step (2), the resulting mixture is cured and modified by keeping it in a vacuum environment at 250℃ for 2 hours.

6. The method for preparing phenolic resin-modified pitch-coated graphite anode material according to claim 1, characterized in that: In step (4), the coating precursor is heated to 500°C at a heating rate of 5°C / min and held for 30 min for pre-carbonization; then the temperature is increased to 1000°C at a rate of 5°C / min and held for 120 min to complete the final carbonization.

7. The method for preparing phenolic resin-modified pitch-coated graphite anode material according to claim 1, characterized in that: The solvent removal methods in steps (1), (2) and (3) are all rotary evaporation; preferably, vacuum rotary evaporation.

8. The phenolic resin modified bitumen-coated graphite anode material prepared by the preparation method of the phenolic resin modified bitumen-coated graphite anode material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for preparing modified graphite negative electrode material of lithium ion power battery

    CN103035919A

  • Modified asphalt coated microcrystalline graphite negative electrode material and preparation method thereof

    CN115579470A